INFLUENCE OF PROFITABILITY AND CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE ON FIRM VALUE - Fanisa; Alien Mia Fauzia; Christina Manopo; Tarma; Andhika Ligar Hardika (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This study is to determine the effect of the level of profitability and Corporate Social Responsibility disclosure on firm value. The object of research used in this study is the level of profitability, Corporate Social Responsibility Disclosure, and firm value. The subjects in this study were LQ45 companies listed on the Indonesia Stock Exchange (IDX). This research method is a verification method with a quantitative approach. This study uses secondary data with a sample of 18 LQ45 companies listed on the Indonesia Stock Exchange for an observation period of 2018- 2019 or 36 observations. Testing the hypothesis in this study using multiple regression analysis methods. The results showed that the level of profitability had a significant effect and positive direction, Corporate Social Responsibility disclosure had a positive and significant effect on firm value.